Exploring the Nexus between the Environmental Investment, Environmental Performance, and the Proactive Environmental Strategy in a Supply Chain - Sulaiman Sajilan; Oussama Saoula; Mustafa Rashid Issa; Nasir Abdul Jalil (International Journal of Supply Chain Management, 2019)
The main objective of the current research is to answer the following questions. What role is played by environmental investments in the association between environmentally proactive strategies and environmental performance in supply chain? And in what way the adoption and implementation of environmentally proactive strategies is affected by organizational commitment and customer pressure in the supply chain. The research does not focus on analyzing the variables enabling the occurrence of environmental practices rather it is based on practices, which are environmentally sound. It has been suggested by the previous research studies that the main factors are organizational commitment and customer pressure. The study has used questionnaire adapted from the prior studies to collect the data. The SEM-PLS is used to analyses the collected data. Due to limited research available on the association of corporate environmental practices and supply chains specific to the emerging countries, the data has been collected in the manufacturing industry of Indonesia. The findings of the study have been discussed along with limitations. The research also gives implications for future.